The Influencing Factors of an Effective Maintenance Programme for Heritage Buildings in Batu Pahat, Johor - Mohd Bekeri, Amirul Asyraf; Syed Mohamad, Syed Burhanuddin Hilmi (Recent Trends in Civil Engineering and Built Environment, 2024)
Heritage buildings are among the attractions for tourists who are interested in the history behind the events and figures associated with the heritage buildings. Numerous nineteenth-century heritage building are architectural and urban masterpieces that should be preserved and maintained for future generations to see and experience. The process of preservation of building's original constructed form and architectural characteristics, conservation both maintains and improves its worth. Numerous heritage buildings were in bad condition, with visible signs of significant deficiencies, posing a threat to their survival because heritage building, leading to poor maintenance and management practises, which sooner or later lead to the degradation of all these buildings. Therefore, the aim of this study is to establish find the influence factor in effective maintenance programme and the criteria of effective maintenance programme. The method that has been used in this study is to use a qualitative method that is by collecting information through questionnaires. the Likert scale method was used in preparing the questionnaire. A total of 10 respondents filled in the form. The data obtained were analysed using the averaging index method to obtain the factors and criteria most agreed by all respondents. As a result of the successful data analysis obtained, three factors and criteria of an effective maintenance program were obtained in this study heritage buildings must be conserved and maintained because they have inherent value and importance. In conclusion, heritage building will degrade over time, needing ongoing care and repair to prevent deficiencies and degradation. All maintenance issues that arise should be investigated first in order to identify the elements that contribute to the issues.